ANALYSIS OF POTENTIAL AND ELABORATION OF STATE REGULATION MEASURES TO IMPROVE THE EFFICIENCY OF BEEKEEPING (A CASE STUDY OF THE UDMURT REPUBLIC) - Leonidovna Vorobyeva, Svetlana; Valeryevna Abasheva, Olga; Mullanurovna Kislyakova, Elena; Yuryevna Berezkina, Galina; Ivanovich Kokonov, Sergey (Revista Inclusiones, 2020)
The paper contains analytics on the dynamics of indicators characterizing the efficiency of management in the beekeeping industry of the Russian Federation as a whole and of the Udmurt Republic in particular. The analysis covers the last 50 years. A downward trend in the number of bee colonies has been revealed: decrease by 1.8 times in the Russian Federation and by 3 times in the Udmurt Republic. At the moment, practically the entire industry is concentrated in the private sector; a very low percentage of bee yards belongs to public households. Analysis of beekeeping development potential in the Udmurt Republic shows that forage resources can ensure 5.6 times more honey products. To change the situation in the region, a reorganization of the industry management is required. Measures to improve the mechanism of state management of the beekeeping industry are proposed. They include establishment of an administrative body, responsible for veterinary and statistical check, and development of regulatory framework – a Beekeeping Act. This will enhance the efficiency of beekeeping management, food security (in the framework of the import substitution program) and living standards.